Protein Thiols In The Urine Of Pre-Eclampsia Patients - S.M AWANTI; G.A PATIL; BHUVANENDRANATH.H; SANTOSH JEEVANGI; R.B PATIL (International Journal of Pharma and Bio Sciences, 2011)
Hypertensive disorders of pregnancy are important causes of maternal and fetal mortality & morbidity. Pre-eclampsia is one of them. The presence of oxidative stress in pre-eclampsia is well proven fact. The thiol groups contribute most to the antioxidant status of the body. The plasma thiols were found to be decreased in patients with pre-eclampsia. The current study was designed to know the levels of such protein bound thiols in 8,12 hr urine samples and to correlate with 24 hr urine sample in pre-eclampsia patients. Serum and urine protein thiols were determined by Spectrophotometric method using dithionitrobenzoic acid (DTNB).There was significant increase in protein (p<0.01) and significant decrease in urine protein thiols (p<0.01) in 8, 12 and 24 h urine protein in pre-eclampsia patients. Among 8,12 and 24 hr urine sample in both the groups; 8 and 12 hr urine showed significant decrease in thiols compared to 24 hr urine. These results suggest that determination of total protein of 8 ,12 hour urine samples along with urine protein thiols can be a better alternative for 24 hr urine protein value in the early diagnosis of pre-eclampsia.